Effects of Different Soil Treatments on Weight Gain, Shell Length and Shell Aperture of Snails (Archachatina marginata) - Afomezie, P.I.; Ebenebe, C.I.; Njoku, O.O.; Ufele, A.N.; Okonkwo, J.C. (Pakistan Journal of Nutrition, 2011)
Effects of different soil treatments on the weight gain, shell length and shell aperture of snails raised under standard condition were studied using 180 juvenile snails of similar weights. The snails were randomly assigned into four treatment groups designated as A, B, C and D and NPK fertilizer, Magnesium sulphate and Poultry manure were added at the rate of 1.5 kg/5 kg soil sample to treatments A, B and C, respectively, while treatment group D were placed in untreated soils. The experiment lasted for 176 days, during which the snails were subjected to similar dietary reign and husbandry practices. Data obtained were subjected to ANOVA under a completely randomized design and differences between means were separated using Least Square Significant Difference (LSD). The result show that snails raised on soil treated with poultry droppings performed better in all the parameters studied, followed by those raised in magnesium sulphate treated soil and the least being those raised on NPK treated soil. The study maintained that soil treatment affects snails’ performance and recommends treatment of soil with poultry droppings to enhance snail production and discourages the use of NPK fertilizer in a land where the snail population is importance.